Orbital Performance Simulation of Ring Type Electro Motor Compared with Radial Motor Using Magnet Software - Widya Aryadi; Andri Setiyawan; Riki Sulistyo (Universitas Sultan Ageng Tirtayasa, 2023)
The use of fossil fuels is currently very high, resulting in an increase of CO2 in the atmosphere. The transport sector is currently the largest contributor to the greenhouse effect worldwide. Electric vehicles are the main solution for researchers to develop. This study compares force, torque, and orbital flux of electro-orbital ring-type motors and radial electro-motors. This research uses a simulation method to determine the value of force, torque, and linkage flux in each type of motor using MagNet Software. This research is development research using a simulation approach. The simulation test subjects consisted of computers, MagNet 7.5 software, Solidworks, Calipers, Protractors, and Rulers. There are 3 data collected in this research, and the data are as follows: (1) force, (2) torque, and (3) linkage flux. Data analysis was done by simulating with magnet software and then comparing the test results on the linkage force, torque and flux. The simulation results are then compared to determine the performance of each motor. The result of this research is that the performance of the ring-type orbital electro motor compared to the radial electro motor is better in attractive conditions, but lower in repulsive conditions. In the magnetic attraction condition, the average value ratio of the ring type orbital electro motor compared to the radial electro motor is 1.08:1 force, 1.68:1 torque, and 1:1.03 linkage flux. In the reject condition, the average ratio of ring-type electro motor orbitals compared to radial electro motor is 1:1.3 force, 1:1.06 torque, and 1:1.6 linkage flux.